Salmonberry Bird and Goose Woman: Birds, Plants, and People in Indigenous Peoples' Lifeways in Northwestern North America. Issue Volume 36:Issues 4(2016) (December 2016) - Turner, Nancy J.; Bhattacharyya, Jonaki
Both birds and plants are major components of the world's biocultural diversity. Salient species of both are recognized and named in virtually every language and both feature in countless ways in people's systems of knowledge, practice, and belief, as sources of food, materials, and medicines, and as ceremonial and religious symbols. However, these two major biological groups are also linked together, and their ecological associations are likewise reflected in cultural knowledge systems. In northwestern North America, there are many examples of the intersection of botanical and ornithological knowledge, reflected in people's vocabulary, narratives, belief systems, and management practices. Here we provide diverse illustrations of this intersection in cultural knowledge of plant-bird associations. These examples link together observations of bird habits and habitats with particular plant species and show how this complex integrated knowledge and experience has helped promote cultural richness and well-being for First Peoples of the region. Bird species from swans (Cygnus spp.) to hummingbirds (Trochilidae) and plants from edible root vegetables to nectar-producing flowers are exemplified as major representatives of ethnoecological connections. These relationships remind us of the importance of interspecies ties to environmental and cultural integrity—a key to sustainable living into the future.